(3GdeWQH GdeYQH GdLGeY dCgd GdeTQb hGdeZQHs - (3YHO GdbGOQ Hf Ndjd GdeOfj,J (B1187 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd YdeGA gPg GdCeI GdeMeOjI cCfHjGA Hfi ESQGFjd HJdbhf GdYde Yf Cgdg ceG Jdbi GdhMi Yf LHQjd s
(3BNQgG (B:s
(3hEfeG fSJHTQ HGdSfI GdNdb CbdGe GdMb ,hfSCd Gddg JYGdi GdENdGU djchf SHHkG ehUdkG ddNdGU hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HBNQgG bQGAI SfI (B1237 (3g`s
(3cJHJ GdYfGhjjf HGdMeQIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs